A new species of Bothriochloa (Poaceae, Andropogoneae) endemic to montane grasslands of Santa Catarina, Brazil - Dalmolim, Emilaine Biava; Zannin, Ana (Phytotaxa, 2014)
Bothriochloa catharinensis, a new species of Andropogoneae (Poaceae: Panicoideae, Andropogoneae) endemic to montane grasslands associated with araucaria forest in the state of Santa Catarina, Southern Brazil, is described and illustrated. Morphological similarities between the new taxon and other species of Bothriochloa are discussed. Comments on habitat, morphology, distribution and conservation status are provided.